First record of the Spiny blaasop Tylerius spinosissimus (Regan, 1908) (Tetraodontidae) from the Turkish coasts - TURAN, C.; YAGLIOGLU, D. (Mediterranean Marine Science, 2011)
The non-indigenous tetraodontid of Indo-Pacific origin Tylerius spinosissimus is recorded for the first time in Turkish waters and for the third time in the Mediterranean Sea. This record increases to 53 the number of Indo-Pacific alien fish species present along the coasts of Turkey.